A Cadaveric Study of Superficial Palmar Arch with Surgical Importance - Hemamalini Shetty (JCDR Research and Publications Private Limited, 2021)
Introduction: Arterial supply of hand is by two arterial anastomotic arches formed by radial and ulnar arteries and their branches. The anastomoses between the branches of radial and ulnar arteries such as palmar carpal and dorsal carpal arches at the wrist and superficial and deep palmar arches in the palm, maintain a rich arterial supply to the wrist and palm. Effective collateral circulation in palm is essential in peripheral arterial diseases such as Raynaud’s disease and in harvesting radial artery or the ulnar artery for Coronary Artery Bypass Graft (CABG) surgery. Aim: To observe the variations in the formation of superficial palmar arch. Materials and Methods: A descriptive study was performed on 45 formalin fixed upper limbs of both sex in the Department of Anatomy, JSS Medical College, Mysuru, Karnataka, India. The study was conducted during routine dissection of upper limbs for undergraduates as per the Cunningham’s manual for practical anatomy. Few rare variations in the formation of superficial palmar arch and the arterial pattern of hand were noticed. The variations found were classified according to Coleman and Anson classification. Results: Out of 45 limbs, complete arch was found in 36 limbs and incomplete arch in nine limbs. In complete arch type, we found an arterial arcade, bifurcation of ulnar artery and in incomplete arch type, radial-radial anastomosis. Another rare findings of highly tortuous ulnar artery in forearm and in the palm. Conclusion: The findings in the variations of superficial palmar arch are essential in microvascular surgery, forearm fasciocutaneous flap, radial artery and ulnar artery harvesting in coronary artery bypass graft procedure.